PERSONALIZED TRAINING'S IMPACT ON JOB PERFORMANCE: SERIAL MEDIATION OF LEARNING EFFECTIVENESS AND SKILL DEVELOPMENT - Suwannasin, Siwat (Asian Administration and Management Review, 2025)
In today's dynamic business landscape, organizations seek strategies to enhance employee performance. This study investigates the influence of personalized training programs on job performance, focusing on the mediating roles of learning effectiveness and skill development. Data collected from 366 employees across diverse industries revealed a significant positive impact of personalized training on job performance through the serial mediation of enhanced learning effectiveness and skill development. Both direct and indirect effects contributed to job performance, underscoring the value of tailored training interventions. These findings offer valuable insights for organizations and HR professionals, suggesting that investments in personalized training can yield workforce capabilities and long-term performance benefits. Practical recommendations emphasize adaptive training strategies to meet individual learning needs. This research advocates for personalized training programs to maximize employee potential and drive organizational success.